A comprehensive analysis of three-dimensional normal grain growth of pure iron via multi-phase field simulation (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
A three-dimensional (3D) multi-phase-field model has been established to simulate normal grain growth in pure iron. The advanced visualization technology was used to extract the related data for individual grains, which can clearly display the grain morphology with distinct grain boundary surface as well as the space distribution of neighboring grains．Based on the simulation results, the grain growth kinetics model has been described, which is in conformity with Burke and Turnbull’s parabolic law. The phenomenon of a ‘Hillert regime’ in 3D grain growth and the topological transformation mechanism are investigated. The grain size distributions under different time steps show well agreement with the Hillert distribution. The detailed evolution of grain growth process is extracted, particularly the grain size distribution and the volumetric growth rate. The models of von Neumann-Mullins and Hilgensfeldt for predicting the volumetric growth rate were used for the comparison. The volumetric growth rate is approximately zero when the number of grain sides is 13.7. The average grain side numbers mainly concentrated around 15. The multi-phase field simulation can be used to quantitatively analyze the change of topological relationship of grains with time evolution and reveal the general law of normal grain growth.